'Streetism' or living in the street, an emerging phenomenon as a way of life in developing countries, a case study of children living on the streets of Ghana - Tettegah, Christine A. N. (2012)
There is an alarming increasing number of children living either partially or permanently on the streets of African countries. This research has been undertaken with children who live their lives more permanently on the streets of Accra the capital city of Ghana. The study is focused on their survival strategies and investigates the detail of their day to day lives on the street. In addition, this thesis illustrates the home experiences of these Street children prior to their coming onto the street. These experiences include poverty, neglect and abuse. On the street, the life of the children is full of the struggle for survival and is. characterised by the complexities of the Street Children's vulnerability as well as their resilience. The study reveals interactions and negotiations that go on between Street Children and their community, their peers and other people they come across in their settings, for their mental, emotional and physical wellbeing.